Mid‐ventricular obstructive hypertrophic cardiomyopathy with apical aneurysm: An important subtype of arrhythmogenic cardiomyopathy. Issue 5 (9th February 2019) - Cui, Li; Tse, Gary; Zhao, Zhiqiang; Bazoukis, George; Letsas, Konstantinos P.; Korantzopoulos, Panagiotis; Roever, Leonardo; Li, Guangping; Liu, Tong
Abstract: Mid‐ventricular obstructive hypertrophic cardiomyopathy (MVOHCM) is an uncommon type of HCM. LV apical aneurysms are present in more than 20% MVOHCM cases and has been identified as an independent predictor of potentially lethal arrhythmic events, including non‐sustained or sustained ventricular tachycardia (VT), and ventricular fibrillation (VF), as well as SCD. Although the pathogenesis of LVA remains unknown, but it has been suggested that apical aneurysm may be secondary to the increased after‐load and high apical pressure arising from significant pressure gradient of the midventricular obstruction. The scarred rim of the aneurysm and the adjacent areas of LV myocardial fibrosis and consequent apical oxygen‐demand mismatch may be responsible for the formation of apical aneurysm. Recent electrophysiologic studies have demonstrated that the aneurysmal rim forms the primary culprit arrhythmogenic substrate for generation of monomorphic ventricular tachycardia leading to SCD, but the clinical significance of the size of aneurysm in relation to SCD remains unsettled. We summarized the clinical features of the patients with MVOHCM and apical aneurysms. Appropriate therapeutic interventions include ICD implantation, and early surgical intervention for gradient relief may be undertaken to relief the MVO.